FINANCIAL BOOTSTRAPPING DAN KINERJA UMKM: PERAN MODERASI LITERASI KEUANGAN - Chintya Wira Dika; Maria Rio Rita; Imanuel Madea Sakti (Jurnal Kewirausahaan dan Bisnis, 2021)
The classic problem faced by MSMEs is limited access to funds from banks. This makes MSMEs to look for alternative strategy, one of which is through financial bootstrapping. This study aimed to examine the effect of financial bootstrapping on the performance of MSMEs with financial literacy as a moderator. The research sample were 38 MSME owners in Salatiga City, which were tested by Moderated Regression Analysis (MRA). The results showed that financial bootstrapping had a negative effect on the performance of MSMEs and the moderating role of financial literacy were proven. This means that when financial bootstrapping is supported by financial literacy from business actors, business performance will increase.Key words: Financial Bootstrapping, Financial Literacy, MSMEs Performance